Electrical characteristics of magnetic memory cells comprising magnetic tunnel junctions and GaAs diodes - Boeve, H; Sousa, R C; Freitas, P P; De Boeck, J; Borghs, G (Electronics letters, 2000)
Magnetic tunnel junctions have been the subject of a study for use in nonvolatile magnetic memories. To cancel leakage paths in the memory array, a semiconductor switch is integrated per cell. Successful integration with GaAs diodes, dominating the cell performance, is described. Good resistance matching between both elements is essential to optimise the output characteristics, i.e. the absolute voltage or current difference between the two magnetic states.